THE INFLUENCE OF SEAMLESS AND COMPLETENESS DISCHARGE SUMMARY FILLING TO SUITABILITY OF SEVERITY LEVEL IN TERTIARY REFERRAL HOSPITAL - Dian Fajar Hapsari, Dian
Abstract Background: The implementation of the national health insurance program to fulfill the payment system related to a claim needs the documentation of services in the discharge summary. The discharge summary’s content becomes the basis for determining the code of disease especially the suitability between diagnoses and examination to determine the severity level of disease.